Biomechanical analysis of throwing skills - Zhou, X. L.; Zhao, F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction One of the most important tasks of the Chinese track and field center is to improve the performance level of Chinese throwing athletes. In May 2002, we started a research programme entitled "fast image manipulation and feedback of the throwing skill". Using kinematical analysis, we investigated the throwing action in shot put, discus and javelin and we identified the athletes` individual throwing characteristics, skill level, and the existing problems with their technique. Based on these it is possible to suggest training programmes and measures for improving the skills of the athletes with the cooperation of the coaches. Methods The three dimensional (3D) analysis of the throwing skill is achieved by tracking the 3-D movement of the athlete body and the implement. The relevant parameters describing the quality of the throwing action can be calculated, inspected and analysed in just a few minutes after the throw, by running the fast-feedback software programmed by ourselves. This system allows the display and reproduction of the athletes` 3-D movements and can show these movements from every viewing angle in the 3-D space. Thus, it can help the coach to visualise better the movement that the athlete performed as seen from different directions and help them to identify any technique faults. The expert system based software for the throwing skill analysis was developed and programmed in house by the authors. Results and Discussion Using the above system we analysed the performance of the expert shot put athlete Meiju Liu. It was found that one of the technique faults was during the final `energising` phase caused by the right deflection of left foot, and after correction of the movement the final energising was more stretched. In the discuss throw, the main common problem of the athletes was that the discus speed declined considerably during the phases of `empty out` and the transition. Various ways to solve the problem were discussed with the coach. In the javelin throwing as well, this system was used to analyse individual throwing skills and after extensive discussion with the coaches, to select an optimal throwing skill model for each athlete.